Distribution and geochemical partitioning of heavy metals in sediments of the Bahía Blanca estuary, Argentina - Marcovecchio, Jorge Eduardo (2005)
A long-term study programme has evaluated heavy metals in the Bahı ́a Blanca estuary, considering occurrence, concentration and distribution in the estuarine sediments, as well as their corresponding geochemical partitioning in the , 62 m m grain size fraction of the sediment. Total concentrations of heavy metals (Cd, Zn, Cu, Cr, Pb, Fe) have been determined through flameless atomic absorption spectrophotometry (AAS). Geochemical partitioning of these metals was determined following a sequential extraction technique. Furthermore, heavy metal distribution was stud- ied against organic matter concentration within the sediments. The results allow the characterization of the spatial distribution of the metals, together with their accumulation areas and potential sources. Bahı ́a Blanca estuarine sediments have low to medium heavy metal concentrations. The geochemical partitioning indicated that many bioavailable species occur within the system, including those of highly toxic elements such as cadmium. Moreover, a theoretical scheme of transference of these metals to other compartments within the system was proposed. Finally, the environmental status of the estuary was addressed within the described framework.